The comparison between the market value (MVA) the net profit after tax by economic value added (EVA) to net profit after tax of the companies listed on the in Tehran Stock Exchange - Ashtiani, Saleh Payande; Ashtiani, Amir Rahimi (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
Desired performance and eventually increase the company's value will increase shareholder wealth. The fundamental challenge of managing businesses to create value for shareholders. The comparison between the market value (MVA) the net profit after tax by economic value added (EVA) to net profit after tax of the companies listed on the in Tehran Stock Exchange in 2007 to 2014. So that can be a benchmark internal performance evaluation that a representative of the market value is also achieved which the statistical was determined technique of a linear regression coefficient, And EVIEWS and SPSS software was used to test the hypotheses. The results show that there are positive correlation between (MVA/EARING) as the dependent variable (EVA/EARING) as independent variables studied in all companies, regardless of their weakness. So the companies listed in in Tehran Stock Exchange (EVA/EARING) as a measure of internal performance measurement alone is not enough to predict the effectiveness criteria is value in the market. In our group of companies and industries except, automotive and pharmaceutical industries that there were not a significant relationship between the variables in the rest of the industry significant relationship between the variables.